Building a SAN-less Private Cloud with IBM PowerVM and IBM PowerVC - Vetter, Scott; Lazcano, Javier; Lutz, Stephen (IBM Redbooks, 2018)
This IBM® Redpaper™ publication describes a software-defined infrastructure (SDI) solution with IBM PowerVC. In IBM PowerVC SDI, you combine scale-out IBM Power Systems™ servers with software that creates the whole stack that is needed to provide virtual machines (VMs) for applications such as open source databases or Hadoop. The SDI solution uses base IBM Power Systems technologies such as IBM PowerVM® NovaLink and the open source hypervisor kernel-based virtual machine (KVM). The solution combines with sophisticated storage technologies, such as IBM Spectrum™ Scale, and with the powerful networking capabilities that are provided by the Open vSwitch (OVS) technology. IBM PowerVC "hides" much of this software so that it is not apparent to your daily cloud operations. By using IBM PowerVC, you can manage scale-out SDI-based systems along with traditional PowerVM systems. This publication describes how to install and configure the SDI solution using PowerVM and IBM PowerVC running on the Power Systems platform. This publication also presents the essentials to help existing Power Systems technical specialists use existing "under the covers" disk space to build a cost-effective cloud solution.